Extended self: spontaneous activation of medial prefrontal cortex by objects that are ‘mine’ - Kim, Kyungmi (Oxford University Press, 2014)
The concept of extended self refers to the idea that people incorporate self-relevant others or objects into one’s sense of self. Initial neural support for the notion of extended self was provided by fMRI evidence that medial prefrontal cortex (MPFC) showed greater activation while people imagined objects belonging to them compared with someone else (Kim & Johnson, 2012). This study investigated whether self-associated objects (i.e. ‘mine’) subsequently engage MPFC spontaneously when a task does not require explicit self-referential judgments. During fMRI scanning, participants detected ‘oddballs’ (objects with a specific frame color) intermixed with objects participants had previously imagined belonging to them or to someone else and previously unseen non-oddball objects. There was greater activity in MPFC and posterior cingulate cortex for those ‘self-owned’ objects that participants were more successful at imagining owning compared with ‘other-owned’ objects. In addition, change in object preference following the ownership manipulation (a mere ownership effect) was predicted by activity in MPFC. Overall, these results provide neural evidence for the idea that personally relevant external stimuli may be incorporated into one’s sense of self.